APPLICATION OF LEGO PLAY THERAPY TO REDUCE ANXIETY LEVELS IN PRESCHOOL CHILDREN DUE TO HOSPITALIZATION - Budiyati, Budiyati; Firmansyah, Bayu (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Anxiety is one of the responses of preschoolers who are undergoing hospitalization. Hospitalization often causes trauma to the child and sometimes makes the child cry, and refuses to cooperate during treatment. To overcome anxiety in preschoolers, the role of nurses in providing interventions must pay attention to the needs of children according to their growth and development. One of the activities to reduce anxiety in preschoolers is to provide lego play therapy. The purpose of proving EBNP by applying lego play therapy to reduce anxiety levels in preschool children in the age range of 3-6 years who are undergoing hospitalization. The design used is a descriptive method involving 3 respondents of preschool children, the instrument used is using the Preschool Anxiety Revised Scale (PASR) questionnaire. The action given is lego play therapy 6 times for 3 days with a duration of 20-30 minutes. The conclusion is that there is an effect of Lego play therapy on anxiety levels in children aged 3 – 6 years during hospitalization.